Preparation method of plastic source flash evaporation graphene-based multifunctional anticorrosive paint

By mixing plastic powder with conductive carbon black for Joule heat reaction, flash graphene was prepared and combined with epoxy resin, the existing graphene anticorrosion coatings were solved, and the problems of high cost, complex operation and poor dispersion uniformity were achieved. Low-cost and efficient preparation of anticorrosion coatings improves anticorrosion performance and photothermal deicing effect.

CN119490782APending Publication Date: 2025-02-21QUZHOU RES INST OF ZHEJIANG UNIV

Patent Information

Application Number
CN202411601744.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing graphene anticorrosion coatings have shortcomings in the problems of high cost, complex operation and poor dispersion uniformity, and graphene may aggravate metal corrosion and affect its application.

Method used

Flash graphene was prepared by mixing plastic powder with conductive carbon black for a Joule thermal reaction, and combining it with epoxy resin to prepare a multifunctional anticorrosion coating. This method uses instantaneous discharge of capacitors to generate Joule heat, quickly rise and fall, and forms high-quality flash graphene, which improves its dispersion and corrosion resistance in epoxy resin.

Benefits of technology

The preparation of low-cost, simple-to-operate graphene-epoxy resin composite coating is achieved, which improves the anti-corrosion performance and photothermal deicing effect of the coating, and avoids the problem of graphene intensifying corrosion on the metal surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490782A_ABST
    Figure CN119490782A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a plastic source flash graphene-based multifunctional anticorrosive coating, which comprises the following steps: mixing plastic powder and conductive carbon black to obtain mixed powder, and carrying out Joule thermal reaction on the mixed powder to obtain flash graphene; grinding the flash graphene, adding a polypyrrolidone solution, and carrying out ultrasonic dispersion, filtration and drying; adding the obtained dispersed flash graphene into an acetone solvent, ultrasonically dispersing uniformly, then adding epoxy resin, stirring until the epoxy resin is dissolved, and finally adding a curing agent to obtain the multifunctional anticorrosive coating. According to the preparation method, waste plastic can be effectively utilized, so that the multifunctional anti-corrosion coating with relatively good anti-corrosion performance and photo-thermal deicing effect is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a method for preparing a plastic-source flash-evaporated graphene-based multifunctional anti-corrosion coating. Background Art

[0002] Metal materials are an important foundation for promoting the development of human society and are widely used in machinery manufacturing, transportation and daily life of residents. It is estimated that the direct economic losses caused by metal corrosion in the world are as high as 700 billion to 1 trillion US dollars each year, which is 4 to 6 times the total of other natural disasters. The equipment scrapped due to rust each year is equivalent to 30% of the world's total annual steel production.

[0003] Epoxy resin (EP) is widely used in the field of corrosion protection due to its easy processing and molding, excellent curing performance and strong mechanical properties. However, it still has many problems such as easy failure during use. In order to improve the corrosion resistance of epoxy resin anti-corrosion coatings, nano-modified particles such as graphene can be added to improve the function of epoxy resin.

[0004] The invention patent application with the publication number CN117965077A discloses "a method for preparing a melamine-modified graphene oxide anti-corrosion coating", which introduces a method for preparing a melamine-modified graphene oxide anti-corrosion coating, wherein graphene oxide is prepared by dispersing a graphene oxide-polyphosphoric acid solution into a melamine ethanol dispersion, and adding yttrium vanadate to catalyze the reaction to modify the graphene oxide, thereby greatly reducing the disorder of the modified graphene oxide sheet and further improving the corrosion resistance. However, due to the high price of graphene oxide and the complicated and energy-intensive chemical modification steps, its application in corrosion coatings is limited.

[0005] The invention patent application with the publication number CN114907712A discloses "a method for preparing a graphene anticorrosion coating", which introduces a method for preparing a graphene anticorrosion coating, including firstly modifying graphene oxide in an acid-base solution system, adding polyisocyanate to react at high temperature, then adding polyol, catalyst and chain extender to react at high temperature of 150℃-200℃ under nitrogen protection, adding silane coupling agent, deionized water and ethylenediamine to emulsify and react to obtain a graphene anticorrosion coating for the surface anticorrosion of NdFeB permanent magnets. The invention patent application with the publication number CN105568243A discloses "a method for preparing a graphene anticorrosion coating for stainless steel surface", which uses natural graphite as raw material, prepares graphene powder by oxidation-reduction method, puts the graphene powder in a tablet press to press into a graphene film for ion sputtering, and covers it on the surface of the stainless steel sample to obtain a graphene anticorrosion coating. These methods and technical solutions are cumbersome, and have high requirements for equipment and low production efficiency.

[0006] In addition, although graphene is an excellent protective material, it also has adverse side effects, namely that graphene can aggravate metal corrosion, which may hinder its application in metal protection. In addition, graphene is very easy to agglomerate in coatings and even produce more micropores. Its dispersion uniformity is also a bottleneck for the widespread use of graphene.

[0007] Therefore, it is urgent to develop a low-cost, simple-operation, green and efficient method for preparing composite graphene-epoxy resin multifunctional coatings. Summary of the invention

[0008] The present invention provides a method for preparing a plastic-source flash-evaporated graphene-based multifunctional anti-corrosion coating, which can effectively utilize discarded plastics to obtain a multifunctional anti-corrosion coating with good anti-corrosion performance and photothermal deicing effect.

[0009] The present invention provides a method for preparing a plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating, comprising:

[0010] (1) mixing plastic powder and conductive carbon black to obtain a mixed powder, and subjecting the mixed powder to a Joule heat reaction to obtain flash graphene;

[0011] (2) grinding the flash-evaporated graphene, adding a polypyrrolidone solution, ultrasonically dispersing, filtering, and drying;

[0012] (3) adding the dispersed flash graphene obtained in step (2) into an acetone solvent, uniformly dispersing it by ultrasonication, then adding epoxy resin, stirring until the epoxy resin is dissolved, and finally adding a curing agent to obtain a multifunctional anti-corrosion coating.

[0013] Preferably, in the multifunctional anticorrosion coating, the content of the flashed graphene is 0.3-0.9wt%. The present invention controls the content of the flashed graphene so that the prepared anticorrosion coating has a higher photothermal deicing effect and improved anticorrosion performance. If the content is too low, the corrosion improvement effect is not significant; if the content is too high, the graphene will be unevenly dispersed and agglomerated, which will destroy the coating structure and accelerate corrosion.

[0014] Preferably, the mass ratio of the plastic powder to the conductive carbon black is 5 to 10:1. The addition of carbon black can reduce the material resistance, thereby ensuring the normal discharge and temperature rise of the Joule heat device. If the content is too low, the resistance of the reaction material will be too large, the current will be too small, and the temperature cannot reach above 2000K within the reaction time. The carbon chain structure inside the plastic macromolecule cannot be quickly dehydrogenated and rearranged to obtain graphene with a high degree of graphitization and an orderly structure, thereby reducing the dispersibility of the prepared graphene in the intermolecular channel of the epoxy resin; if the content is too high, the raw material cost will increase, the mass of the plastic powder processed in a single time will decrease, and the conversion efficiency of the plastic powder will decrease.

[0015] Preferably, the mesh number of the plastic powder is 80-100 meshes, and the mesh number of the conductive carbon black is 100-120 meshes. If the mesh number of the raw material powder is too small, the energy consumption of the pulverizing process will be increased, and it will be easily washed out by a large amount of gas generated instantaneously during the reaction process, thereby causing material loss and reducing the graphene yield; if the mesh number of the raw material powder is too large, a large amount of energy will be lost due to the need to melt large particles of plastic, reducing the actual heating temperature, and failing to provide sufficient energy to rapidly dehydrogenate and rearrange the carbon chain structure inside the plastic macromolecule to obtain graphene with a high degree of graphitization and an ordered structure, thereby reducing the dispersibility of the prepared graphene in the intermolecular channels of the epoxy resin.

[0016] Preferably, the material of the plastic powder is one or more of polyethylene, polystyrene and polypropylene.

[0017] Preferably, subjecting the mixed powder to a Joule heat reaction to obtain flash graphene comprises the following steps:

[0018] Put the mixed powder into a quartz tube, add graphite plugs at both ends of the mixed powder, then put the quartz tube into a reactor, connect electrodes at both ends of the graphite plug, and press the graphite plug to control the resistance to 1Ω~2Ω;

[0019] Flash graphene is obtained by applying instantaneous capacitor discharge to plastic powder, wherein the voltage is 130-160V, the capacitance value is 90mF, and the circuit opening time is 2.5s.

[0020] Preferably, the mass / volume ratio of the flash graphene to the polypyrrolidone solution is 0.1-1:1 mg / mL.

[0021] Preferably, the mass / volume ratio of the epoxy resin to the acetone solution is 1-2:1 mg / mL.

[0022] Preferably, the mass ratio of the epoxy resin to the curing agent is 2.5 to 3:1.

[0023] Preferably, the curing agent is polyamide D-31, and the epoxy resin is Epon828.

[0024] The inventive principle of the present invention is described as follows:

[0025] The present invention provides a method for preparing a plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating, which generates Joule heat by discharging a material through a capacitor group, and is a resistance / ohm heating process. By heating and cooling the material at a rate of 2000-3000K / s in a very short time, the plastic molecules are rapidly dehydrogenated by chain breaking, and the current passes through the material to promote the rearrangement of the carbon structure, so that the amorphous carbon is converted into high-quality flash-evaporated graphene with a distinct lamellar structure. The turbine-shaped structure obtained by superimposing multiple lamellar layers makes the graphene converted from the plastic have excellent dispersibility in the organic system, so that it does not require an additional redox process and can be directly mixed with epoxy resin. Due to the nano-lamellar structure of graphene, it can block the micro-crack channels of epoxy resin, greatly improving the anti-corrosion performance of epoxy resin. At the same time, graphene has extremely high photothermal conversion efficiency, thermal conductivity and hydrophobicity, so that the corrosion coating also has a photothermal deicing effect.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention uses Joule heat reaction to increase and decrease the temperature in a very short time, so that the plastic molecules are quickly chain-broken and dehydrogenated to promote the rearrangement of the carbon structure, forming a flash graphene with a turbine-shaped structure obtained by stacking multiple layers. The flash graphene with this structure has an excellent dispersion effect in the epoxy resin solution and can block the micro-crack channels of the epoxy resin, thereby greatly improving the corrosion resistance of the epoxy resin.

[0028] At the same time, because graphene has extremely high photothermal conversion efficiency, thermal conductivity and hydrophobicity, the anti-corrosion coating produced also has photothermal deicing effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A flow chart of the preparation of a flash graphene anti-corrosion coating provided by an embodiment of the present invention;

[0030] Figure 2 Raman spectrum of flash evaporated graphene obtained in Example 1 of the present invention;

[0031] Figure 3 TEM image of flash graphene prepared in Example 1 of the present invention;

[0032] Figure 4 Comparison of electrochemical curves of the anti-corrosion coatings prepared in Examples 1-3 of the present invention, Cu coated with epoxy resin coatings, and Cu substrate in 3.5wt% NaCl solution;

[0033] Figure 5 Comparison of electrochemical polarization curves of the anti-corrosion coatings prepared in Examples 1-3 of the present invention, Al coated with epoxy resin coatings, and Al substrate in 3.5wt% NaCl solution;

[0034] Figure 6 A graph showing the deicing of the anticorrosive coatings and epoxy resin coatings prepared in Examples 1-3 of the present invention, and Cu substrates frozen at -10°C and irradiated with sunlight;

[0035] Figure 7 Infrared temperature diagrams of the anti-corrosion coatings and epoxy resin coatings prepared in Examples 1-3 of the present invention, and Cu substrates before and after photothermal deicing. DETAILED DESCRIPTION

[0036] Example 1

[0037] The preparation method of a plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating of the present invention comprises the following steps: Figure 1 As shown:

[0038] (1) Mix 80-100 mesh polyethylene / polystyrene / polypropylene mixed plastic and 100 mesh carbon black in a ratio of 5:1. Take 0.2g of the above mixed material and put it into an 8mm inner diameter quartz tube, press it with 8mm diameter graphite plugs at both ends, put it into the reaction box sleeve fixing frame, rotate the electrode rod knob to move it, gently compress and measure the resistance at both ends, and control the resistance to between 1 and 2Ω by controlling the tightness of the compressed material. Install the temperature probe, close the vacuum box, and evacuate the box to reduce the air pressure in the box to 0.02MPa.

[0039] (2) Apply instantaneous capacitor discharge to the plastic powder, set the flash DC discharge voltage to 170V, the capacitance value to 90mF, set the circuit opening time to 2.5s, and detect the temperature in the quartz tube. After the discharge is completed, cool to room temperature, take out the quartz tube, pour out the gray-black powder after the reaction, weigh it, and collect it.

[0040] (3) Grinding the product and adding it into a PVP solution for uniform ultrasonic dispersion, wherein the ratio of graphene to PVP is 1:1, to reduce agglomeration, filtering and drying, and collecting the flash-evaporated graphene powder.

[0041] (4) Add the flashed graphene to the acetone solution, disperse it evenly by ultrasonication, then add the epoxy resin, stir until the epoxy resin is completely dissolved, finally add the curing agent, and mix evenly to obtain the flashed graphene anti-corrosion coating. The amount of graphene and acetone solution is 0.03 g and 10 mL respectively, the amount of epoxy resin added is 10 g, the curing agent is polyamide, and the amount of curing agent added is 3.3 g.

[0042] Example 2

[0043] A method for flash-evaporating a plastic source graphene-based multifunctional anti-corrosion coating of the present invention comprises the following steps:

[0044] (1) Mix 80-100 mesh polyethylene / polystyrene / polypropylene mixed plastic and 100 mesh carbon black in a ratio of 5:1. Take 0.2g of the above mixed material and put it into an 8mm inner diameter quartz tube, press it with 8mm diameter graphite plugs at both ends, put it into the reaction box sleeve fixing frame, rotate the electrode rod knob to move it, gently compress and measure the resistance at both ends, and control the resistance to between 1 and 2Ω by controlling the tightness of the compressed material. Install the temperature probe, close the vacuum box, and evacuate the box to reduce the pressure in the box to 0.02MPa.

[0045] (2) Apply instantaneous capacitor discharge to the plastic powder, set the flash DC discharge voltage to 170V, the capacitance value to 90mF, set the circuit opening time to 2.5s, and detect the temperature in the quartz tube. After the discharge is completed, cool to room temperature, take out the quartz tube, pour out the gray-black powder after the reaction, weigh it, and collect it.

[0046] (3) Grinding the product and adding it into a PVP solution for uniform ultrasonic dispersion, wherein the ratio of graphene to PVP is 1:1, to reduce agglomeration, filtering and drying, and collecting the flash-evaporated graphene powder.

[0047] (4) Add the flashed graphene to the acetone solution, disperse it evenly by ultrasonication, then add the epoxy resin, stir until the epoxy resin is completely dissolved, finally add the curing agent, and mix evenly to obtain the flashed graphene anti-corrosion coating. The amount of graphene and acetone solution is 0.06 g and 10 mL respectively, the amount of epoxy resin added is 10 g, the curing agent is polyamide, and the amount of curing agent added is 3.3 g.

[0048] Example 3

[0049] A method for flash-evaporating a plastic source graphene-based multifunctional anti-corrosion coating of the present invention comprises the following steps:

[0050] (1) Mix 80-100 mesh polyethylene / polystyrene / polypropylene mixed plastic and 100 mesh carbon black in a ratio of 5:1. Take 0.2g of the above mixed material and put it into an 8mm inner diameter quartz tube, press it with 8mm diameter graphite plugs at both ends, put it into the reaction box sleeve fixing frame, rotate the electrode rod knob to move it, gently compress and measure the resistance at both ends, and control the resistance to between 1 and 2Ω by controlling the tightness of the compressed material. Install the temperature probe, close the vacuum box, and evacuate the box to reduce the pressure in the box to 0.02MPa.

[0051] (2) Apply instantaneous capacitor discharge to the plastic powder, set the flash DC discharge voltage to 170V, the capacitance value to 90mF, set the circuit opening time to 2.5s, and detect the temperature in the quartz tube. After the discharge is completed, cool to room temperature, take out the quartz tube, pour out the gray-black powder after the reaction, weigh it, and collect it.

[0052] (3) Grinding the product and adding it into a PVP solution for uniform ultrasonic dispersion, wherein the ratio of graphene to PVP is 1:1, to reduce agglomeration, filtering and drying, and collecting the flash-evaporated graphene powder.

[0053] (4) Add the flashed graphene to the acetone solution, disperse it evenly by ultrasonication, then add the epoxy resin, stir until the epoxy resin is completely dissolved, finally add the curing agent, and mix evenly to obtain the flashed graphene anti-corrosion coating. The amount of graphene and acetone solution is 0.09 g and 10 mL respectively, the amount of epoxy resin added is 10 g, the curing agent is polyamide, and the amount of curing agent added is 3.3 g.

[0054] Results characterization:

[0055] (1) Raman spectroscopy characterization of graphene prepared by flash evaporation of mixed plastics: Figure 2 As shown, the Raman spectrum ID / IG of the flash graphene prepared in Example 1 is only 0.2, 2D / I G The value is 0.6, which is consistent with the Raman spectroscopy characteristics of graphene.

[0056] (2) TEM characterization of graphene prepared by flash evaporation of mixed plastics: Figure 3 As shown, the turbine-shaped multilayer structure of graphene prepared in Example 1.

[0057] (3) Figure 4 As shown, electrochemical polarization curve tests were carried out using a 3.5wt% NaCl solution to simulate a seawater environment to obtain corrosion rates of different coatings, and polarization curves of uncoated copper plates (Cu), copper plates coated with pure epoxy resin (Cu-O), copper plates coated with epoxy resin coatings prepared in Example 1 with 0.3wt% flash graphene added (Cu-O-FG), and copper plates coated with epoxy resin coatings with 0.3wt% ordinary graphene added (Cu-OG) were obtained. The Tafel polarization curves of copper plates coated with anti-corrosion coatings prepared with ordinary graphene (Cu-OG) and anti-corrosion coatings prepared with flash graphene (Cu-O-FG) in saline solution were compared. After untreated ordinary commercial graphene was added to the epoxy resin coating, the anti-corrosion efficiency decreased. The anti-corrosion coating prepared by flash graphene provided in the embodiment can well solve the problem of incompatibility with epoxy resin and improve the anti-corrosion efficiency of the epoxy resin coating.

[0058] (4) Figure 5As shown, the anti-corrosion coatings prepared by Examples 1 to 3 are coated on aluminum plates, and the corresponding polarization curves are Al-O-0.3C, Al-O-0.6C, and Al-O-0.9C, respectively; and the epoxy resin solution is coated on the aluminum plate, and the corresponding polarization curve is Al-O, as well as the aluminum plate, the polarization curve of which is Bare-Al. It can be seen that the anti-corrosion coatings prepared by Examples 1 to 3 have good anti-corrosion properties, and the anti-corrosion coating prepared by Example 3 has the best performance.

[0059] (6) Figure 6 and Figure 7 As shown, a deicing test was carried out on the ice coating under sunlight on a -10℃ ice tray. The flash graphene composite epoxy resin coating prepared in Examples 1 to 3 coated on the Cu substrate can significantly reduce the deicing time, while the deicing effect of the Cu substrate (Bare-Cu) and only the epoxy resin coated on the Cu substrate (0wt%) is poor. The deicing time of the coating with the addition of flash graphene is shortened by more than 50%, and the photothermal heating rate is increased by more than 30%.

[0060] From the Raman spectrum and TEM characterization, it can be seen that the flash graphene has a turbine-shaped nanosheet structure.

[0061] In salt water electrochemical tests, coatings with added flash graphene can significantly improve the anti-corrosion efficiency of the coating. At the same time, as the amount of flash graphene added increases, the anti-corrosion efficiency of the coating continues to improve.

[0062] The flash graphene composite epoxy resin coating also has the benefit of photothermal deicing, which can significantly shorten the photothermal deicing time.

[0063] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the scope of protection of the claims of this patent application.

Claims

1. A method for preparing a plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating, characterized in that: include: (1) mixing plastic powder and conductive carbon black to obtain a mixed powder, and subjecting the mixed powder to a Joule heat reaction to obtain flash graphene; (2) grinding the flash-evaporated graphene, adding a polypyrrolidone solution, ultrasonically dispersing, filtering, and drying; (3) adding the dispersed flash graphene obtained in step (2) into an acetone solvent, uniformly dispersing it by ultrasonication, then adding epoxy resin, stirring until the epoxy resin is dissolved, and finally adding a curing agent to obtain a multifunctional anti-corrosion coating.

2. The method for preparing the plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating according to claim 1, characterized in that: In the multifunctional anti-corrosion coating, the content of the flash graphene is 0.3-0.9wt%.

3. The method for preparing the plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating according to claim 1, characterized in that: The mass ratio of the plastic powder to the conductive carbon black is 5 to 10:

1.

4. The method for preparing the plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating according to claim 1, characterized in that: The mesh number of the plastic powder is 80-100 meshes, and the mesh number of the conductive carbon black is 100-120 meshes.

5. The method for preparing the plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating according to claim 1, characterized in that: The material of the plastic powder is one or more of polyethylene, polystyrene and polypropylene.

6. The method for preparing the plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating according to claim 1, characterized in that: The mixed powder is subjected to Joule heat reaction to obtain flash graphene, comprising the following steps: The mixed powder is put into a quartz tube, and graphite plugs are installed at both ends of the mixed powder. Then the quartz tube is placed in a reactor, electrodes are connected at both ends of the graphite plug, and the graphite plug is pressed to control the resistance to 1Ω to 2Ω; Flash graphene is obtained by applying instantaneous capacitor discharge to plastic powder, wherein the voltage is 130-160V, the capacitance value is 90mF, and the circuit opening time is 0.1-1s.

7. The method for preparing the plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating according to claim 1, characterized in that: The mass / volume ratio of the flash graphene to the polypyrrolidone solution is 0.1-1:1 mg / mL.

8. The method for preparing the plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating according to claim 1, characterized in that: The mass / volume ratio of the epoxy resin to the acetone solution is 1-2:1 mg / mL.

9. The method for preparing the plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating according to claim 1, characterized in that: The mass ratio of the epoxy resin to the curing agent is 2.5 to 3:

1.

10. The method for preparing the plastic source flash-evaporated graphene-based multifunctional anti-corrosion coating according to claim 1, characterized in that: The curing agent is polyamide D-31, and the epoxy resin is Epon828.

Citation Information

Patent Citations

  • Preparing method of graphene anticorrosive coating for stainless steel surface

    CN105568243A

  • Preparation method of graphene anticorrosive paint

    CN114907712A

  • Preparation method of melamine modified graphene oxide anti-corrosion coating

    CN117965077A

  • Preparation method for graphene modified anticorrosive paint

    CN105778716A

  • Graphene heavy-duty anti-corrosion paint, preparation method thereof and heavy-duty anti-corrosion coating

    CN110791167A

Cited By

  • Method for co-processing waste incineration fly ash based on ultrafast carbon thermal reduction

    CN121649208A